PENGARUH LEMBAR KERJA SISWA BERBASIS PQ4R TERHADAP HASIL BELAJAR IPA FISIKA KELAS VIII SMPN 1 LINGGO SARI BAGANTI - Nessa Anugra Rahmi (Universitas Negeri Padang, 2013)
Learning in school still not involve active participation of students. so that student learning outcomes in the cognitive domain is still low, because many students are simply stunned and did not participate in the study, which is done by applying alternative based LKS PQ4R provide opportunities for students to interact, engage actively in learning activities. This study aimed to investigate the effect of LKS PQ4R Based on the results of science learning physics class VIII SMP N 1 Linggo Sari Baganti. Type of research is quasi-experimental research by design